Effects of Dietary Aspergillus Meal Prebiotic on Turkey Poults Production Parameters and Bone Qualities - Reginatto, A.R.; Menconi, A.; Londero, A.; Lovato, M.; Rosa, A. Pires; Shivaramaiah, S.; Wolfenden, A.D.; Huff, W.E.; Huff, G.R.; Rath, N.C.; Donoghue, A.M.; Hargis, B.M.; et al. (International Journal of Poultry Science, 2011)
The objective of this study was to evaluate the effects of 0.2% dietary Aspergillus Meal (AM) on performance and bone parameters of neonatal turkey poults. A total of 200 day-of-hatch turkey poults were used for this experiment. Two dietary treatments, similar in energy and protein content differing only by the addition of 0.2% AM, were used. Poults were divided into 2 treatment groups with 25 birds per treatment and four replicates each. Group 1 received a basal non medicated control diet and group 2 received dietary AM. At the end of 30 d, poults were weighed, euthanized and tibias were collected to evaluate bone quality using an Instron shear press machine and bone parameters such as tibia weight, diameter, ash, calcium and phosphorus assays. Samples of distal ileum were collected and the content subjected to protein and energy analysis. Poults fed with dietary AM had a significant improvement in BW and feed conversion ratios (p